The Effectiveness of Digital Marketing in Efforts to Promote Tlangoh Beach in Bangkalan Madura Through Social Media - Wahyuni, Hera; Bawono, Yudho (Procedia of Social Sciences and Humanities, 2024)
Social media is a tourism information center for tourists regarding various destinations and activities. Social media is the main attraction for attracting tourists and providing various available information, as well as answering various curiosities. The role of ICT in the world of tourism as facilities and infrastructure in promoting tourism which we often hear electronically is called digital marketing. Tlangoh Beach, which is located in Bangkalan, Madura, is a tourist destination that has beautiful views. Based on this, it encourages researchers to conduct research related to strategies for using digital technology as a medium for conveying information in carrying out promotions, building preferences, and increasing visitors to Tlangoh beach in Bangkalan district. The aim of this research is to determine the effectiveness of digital marketing in promoting Tlangoh beach tourism in Bangkalan Regency. This research uses qualitative methods with the AISAS (Attention, Interest, Search, Action, Share) model. The results of this research explain that the existence of social media makes it easier to communicate with potential visitors/tourists. All input and questions received can be used as ideas for future posts and improvements to the Tlangoh Beach tourist attraction. In other words, social media users/readers can provide inspiration for the development of Tlangoh beach tourism in Bangkalan district. It is important to be more interactive with followers or readers of social media because it serves as a form of real actualization of promotional strategies. The use of hashtags in posts on social media is no less important, for example, the hashtag #pantaitlangoh, so all the content in searches for that hashtag on average contains posts about Tlangoh beach.